Offline Media-Based Islamic Education Learning Innovation in the Gadget Restriction Policy at SMK Sulthon Fattah - Naila Fitriah; Dedek Risma; Rifqi Wahyudi; Muhammad Nuzli (Lembaga Yasin AlSys, 2026)
Policies restricting students’ use of personal digital devices have challenged teachers to design engaging and effective learning processes, particularly in Islamic Education learning contexts. This study aims to analyze innovative learning strategies in Islamic Education (Pendidikan Agama Islam) using offline learning media amid restrictions on students’ personal digital device use in Grade XI at SMK Sulthon Fattah. A qualitative case study approach was employed, with data collected through classroom observations and interviews with Islamic Education staff regarding learning activities. The findings reveal that learning innovation was implemented through offline-based visual and audiovisual media, including PowerPoint slides and instructional videos displayed through a projector as a shared screen. This strategy increased students’ attention, participation, and understanding of Islamic Education materials despite the absence of personal digital devices. Its effectiveness lies in its ability to centralize students’ focus on controlled visual learning sources that align with pesantren-based school policies. The study concludes that offline learning media can serve as a strategic solution for fostering contextual and adaptive innovation in Islamic Education while improving the overall quality of the learning process. These findings contribute to Islamic Education pedagogy by demonstrating how offline media-based instruction can support meaningful learning in technology-restricted school environments.